Modelling late stool frequency and rectal pain after radical radiotherapy in prostate cancer patients: Results from a large pooled population. Issue 12 (December 2016) - Cicchetti, A.; Rancati, T.; Ebert, M.; Fiorino, C.; Palorini, F.; Kennedy, A.; Joseph, D.J.; Denham, J.W.; Vavassori, V.; Fellin, G.; Avuzzi, B.; Stucchi, C.; et al.
Highlights: NTCP models were developed for stool frequency/rectal pain after 3DCRT. A pooled population was investigated. More than 1000 patients enrolled. Significant association with large volume receiving medium doses was found. Cardiovascular disease was a risk factor for stool frequency. Abstract: Aim: To investigate late gastrointestinal toxicity in a large pooled population of prostate cancer patients treated with radical radiotherapy. Normal tissue complication probability models were developed for late stool frequency and late rectal pain. Methods and materials: Population included 1336 patients, 3-year minimum follow-up, treated with 66–80 Gy. Toxicity was scored with LENT-SOMA-scale. Two toxicity endpoints were considered: grade ⩾2 rectal pain and mean grade (average score during follow-up) in stool frequency >1. DVHs of anorectum were reduced to equivalent uniform dose (EUD). The best-value of the volume parameter n was determined through numerical optimization. Association between EUD/clinical factors and the endpoints was investigated by logistic analyses. Likelihood, Brier-score and calibration were used to evaluate models. External calibration was also carried out. Results: 4% of patients (45/1122) reported mean stool frequency grade >1; grade ⩾2 rectal pain was present in the TROG 03.04 RADAR population only (21/677, 3.1%): for this endpoint, the analysis was limited to this population. Analysis of DVHs highlighted the importance of mid-range doses (30–50 Gy) for both endpoints. EUDs calculated with n = 1 (OR = 1.04) and n = 0.35 (OR = 1.06) were the most suitable dosimetric descriptors for stool frequency and rectal pain respectively. The final models included EUD and cardiovascular diseases (OR = 1.78) for stool frequency and EUD and presence of acute gastrointestinal toxicity (OR = 4.2) for rectal pain. Conclusion: Best predictors of stool frequency and rectal pain are consistent with findings previously reported for late faecal incontinence, indicating an important role in optimization of mid-range dose region to minimize these symptoms highly impacting the quality-of-life of long surviving patients.